“There’s just such a mismatch”: a qualitative exploration of health systems and organizational-level barriers to accessing cancer services among people experiencing structural marginalization - Tara C. Horrill; Jess Crawford; Scott Beck; Amber Bourgeois; Jagbir Kaur; Leah K. Lambert; Michael McKenzie; Kelli I. Stajduhar; Annette J. Browne (International Journal for Equity in Health)
Abstract Background Within the context of cancer care, access to timely, high-quality care is closely correlated with better health outcomes and quality of life. Yet in Canada, research continues to show that inequities in access to cancer care persist across the cancer continuum, particularly among people experiencing structural marginalization. Although some Canadian research has explored barriers accessing cancer care, little research has explicitly focused on barriers arising from organizational and health systems contexts. Our objective was to explore barriers to accessing cancer services within the health system and organizations delivering cancer services across the cancer continuum for people experiencing structural marginalization. Methods This study drew on critical ethnographic methods, employing a participatory, integrated knowledge translation approach. Data collection included interviews with health and social service providers (n = 24) and key informants (n = 7), interviews and focus groups with individuals with lived experience of significant health and social inequities (n = 29), and 40 h of observations with service providers working in clinical oncology settings. Guided by social justice, critical and intersectional theoretical perspectives, data analysis followed an interpretive descriptive approach. Results Four interrelated themes were developed through our analysis, with the overarching thread of a ‘mismatch evident throughout: (1) the design of cancer services does not always account for social contexts and structural determinants of health; (2) discourses of operational efficiency are competing with equity-oriented care; (3) the physical spaces of cancer care matter; and (4) experiences of stigma and discrimination are incompatible with accessing cancer care. Our findings suggest that the ways in which cancer services across the continuum are designed, including the types of services available, how care activities are structured, what activities take priority, and how services are experienced, create barriers that particularly impact people experiencing structural marginalization. Conclusions Our findings highlight the mismatches between how cancer services are currently designed and delivered, and the specific needs of people experiencing health and social inequities. These findings also point to organizations delivering cancer services as potential sites for transformation toward more equitable access to cancer care. Equity-oriented healthcare may offer a framework for service design and delivery to improve access to cancer care and experiences of care.